Development of recombinant Adeno-Associated Viral vector (rAAV) for passive immunisation against ebola - Tan, T; Rijal, P; Townsend, A; Hyde, S; Gill, D (Elsevier, 2017)
The 2014-2016 Ebola outbreak in West Africa was the largest in history leading to 28,639 cases, of which 40% were fatal. Better treatments and effective vaccines against Ebola virus are needed to prevent future recurrence. Multiple, novel, treatment options were assessed during the outbreak, including ZMapp™ monoclonal antibody therapy, which showed promising results in some patients. However, widespread adoption of this approach is hindered by high costs of monoclonal antibody manufacturing and the relatively short half-life of antibody in the blood circulation. To circumvent such limitations, we propose to utilise recombinant adeno-associated virus (rAAV) delivered to the muscle to express the therapeutic monoclonal antibodies.